Resource-based theory perspective in the textile industry: The impact of the digital supply chain on operational performance - Men, Feng; Yaqub, Rana Muhammad Shahid; Yan, Rui; Irfan, Muhammad; Fatima, Misal e (Frontiers in Environmental Science, 2022)
In a developing nation such as Pakistan, the textile sector is crucial for employment creation and poverty reduction. As a result of digitization, standard industrial operating processes have altered. The study, which is built on resource-based theory, seeks to determine how the digital supply chain (comprised of blockchain, the internet of things, and big data analytics) influences operational performance. In addition, the relationship between the innovative climate and the operational success of the digital supply chain has been analyzed. Data was collected from 270 respondents, i.e., 65 top level managers and 205 middle level managers. The results indicate that the digitization of the supply chain, which includes the application of big data analytics, the internet of things, and blockchain, greatly enhances operational performance. The innovation climate has not been proven to affect operational performance or digitalization. At the end theoretical and practical implication are highlighted.